Use of spatial analysis in the mining field in the Udorka Valley. Introduction to geoarchaeological search for flint workshops at site 24 in Poręba Dzierżna (Małopolska Province, southern Poland) - Binnebesel, Hubert; Sudoł-Procyk, Magdalena (Archaeologia Lituana, 2024)
The prehistoric chocolate flint mine in the Udorka Valley (site 24 in Poręba Dzierżna, Lesser Poland Voivodeship, southern Poland) has been under excavation since 2018. It is the first mine of this raw material discovered outside the Świętokrzyskie Mountains. The currently available dating indicates that the mine was used in the Mesolithic and Neolithic periods.Spatial analysis of artifacts from the fill of the mine shaft allowed for the reconstruction of individual phases of its formation. It also questioned the issue of homogeneity of the assemblage of artifacts from this mining facility and from the overlying layers. Although they are of the workshop type, their simultaneity should be doubted. In order to establish the chronological and cultural framework of flint production in the mining field, it seems necessary to determine the original location of the workshop, which was destroyed and washed out as a result of some kind of runoff. This flow created the sediment that now lies above the shafts, and which is extremely rich in flint artifacts.
Keywords: prehistoric mining; flint workshops; stone age; geoarchaeology; GIS Spatial Analysis